Fabrication of PFO-DBT:OXCBA nanostructured composite via hard template - Fakir, M.S.; Supangat, Azzuliani; Sulaiman, Khaulah (Wiley, 2016)
Poly[2,7-(9,9-dioctylfluorene)-alt−4,7-bis(thiophen-2-yl)benzo-2,1,3-thiadiazole] (PFO-DBT) and o-xylenyl-C60-bisadduct (OXCBA) nanostructured composite has been fabricated via the hard porous alumina template-directed method. Spin-coating technique at the spin rate of 1000 rpm is used to assist the infiltration of polymer solution into porous template. PFO-DBT nanotube is fabricated by replicating the porous alumina template before the formation of PFO-DBT:OXCBA nanostructured composite. Formation of nanostructured composite is completed once the infiltration of OXCBA solution into PFO-DBT nanotubes is achieved. Detailed results of morphological, structural, and optical properties of PFO-DBT nanostructures (nanorods and nanotubes) of different solution concentrations are reported. By tuning the optical properties of PFO-DBT nanostructures, the effect of solution concentration on the optical properties can be realized. The promising PFO-DBT nanotubes are chosen for the further fabrication of OXCBA:PFO-DBT nanostructured composite that acts as a core and shell, respectively. Although the nanostructured composite of PFO-DBT:OXCBA yield low light absorption intensity, the absorption spans the whole visible region and produce low optical energy gap.